2005
DOI: 10.1074/jbc.m501770200
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Sodium Channel Inhibition by AMP-activated Protein Kinase in Oocytes and Polarized Renal Epithelial Cells

Abstract: The epithelial Na ؉ channel (ENaC) regulates epithelial salt and water reabsorption, processes that require significant expenditure of cellular energy. To test whether the ubiquitous metabolic sensor AMP-activated kinase (AMPK) regulates ENaC, we examined the effects of AMPK activation on amiloride-sensitive currents in Xenopus oocytes and polarized mouse collecting duct mpkCCD c14 cells. Microinjection of oocytes expressing mouse ENaC (mENaC) with either active AMPK protein or an AMPK activator inhibited mENa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(178 citation statements)
references
References 60 publications
7
165
1
5
Order By: Relevance
“…When monolayers reached a transepithelial resistance Ͼ1000 ohm-cm 2 (22), cells were incubated in serum-free, supplement-free medium for 24 h prior to treatment. Following treatment for 3 h with ethanol (vehicle) or 1 M aldosterone (Sigma), cells were lysed in 150 l of lysis buffer (10 mM Tris-HCl (pH 7.4), 50 mM EDTA, 0.4% deoxycholate acid, and 1% Nonidet P-40) containing protease inhibitors (1 mM phenylmethylsulfonyl fluoride (PMSF), 1 mM, benzamidine, and 1ϫ Complete Protease Inhibitor Mixture (Roche Applied Science)) and phosphatase inhibitors (25 mM sodium fluoride, 2 M microcystin-LR, and 1ϫ Phosphatase-Inhibitor Mixture Sets I and II (Calbiochem)).…”
Section: Methodsmentioning
confidence: 99%
“…When monolayers reached a transepithelial resistance Ͼ1000 ohm-cm 2 (22), cells were incubated in serum-free, supplement-free medium for 24 h prior to treatment. Following treatment for 3 h with ethanol (vehicle) or 1 M aldosterone (Sigma), cells were lysed in 150 l of lysis buffer (10 mM Tris-HCl (pH 7.4), 50 mM EDTA, 0.4% deoxycholate acid, and 1% Nonidet P-40) containing protease inhibitors (1 mM phenylmethylsulfonyl fluoride (PMSF), 1 mM, benzamidine, and 1ϫ Complete Protease Inhibitor Mixture (Roche Applied Science)) and phosphatase inhibitors (25 mM sodium fluoride, 2 M microcystin-LR, and 1ϫ Phosphatase-Inhibitor Mixture Sets I and II (Calbiochem)).…”
Section: Methodsmentioning
confidence: 99%
“…However, it is not yet clear what the potential upstream regulators of the IKK pathway are in this case. Interestingly, the metabolic sensor AMPK has been reported to be an upstream inhibitor of IKK in several cell systems (37)(38)(39), and we have shown that AMPK inhibits ENaC, also via effects on Nedd4-2 in an AMPK phosphorylation-dependent manner (7,20). Further studies to test for the potential involvement of AMPK and other cellular signaling pathways as upstream regulators of the IKK␤-dependent regulation of ENaC are thus warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids expressing NH 2 -terminal hemagglutinin-tagged and COOH-terminal V5-tagged ENaC subunits were kindly provided by Dr. Thomas Kleyman. HEK-293 and mpkCCD c14 cells were cultured in high glucose, Dulbecco's modified Eagle's medium and defined medium supplemented with hormones and nutrients, respectively, as described previously (7).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations